Environmental capital and sustainable income in Ethiopia - Mohammed Adem (Sustainable Environment)
Conventional GDP measurements often overlooks the significant contribution of the environment to a country’s long-term economic performance, leading to inaccurate assessments and the concealment of important environmental and economic benefits. The aim of this study is to estimate the level of environmental capital and sustainable income. To determine the contribution of environmental capital to GDP, the concept of the neoclassical growth model was used. This analytical approach begins by defining the two types of capital inputs, such as: human capital and environmental capital used in the production of final goods and services. The study found that the total share of environmental capital in GDP was 32% over the study period, while the contribution of environmental capital to gross national production fell from 39% in 2000 to 29% in 2018. The gap between GDP and sustainable GDP estimate also widened between 2003 and 2011. A comparison between GDP and sustainable GDP shows that environmental resource damage can account for up to 15.5% of GDP, leading to an overestimation of GDP. The decline in the share of environmental capital may have long-term implications for the potential of low-income countries to grow sustainably. Therefore, policymakers need to pay adequate attention to environmental capital investments to ensure the long-term sustainability of the economy. Institutions directly involved in GDP estimation also should have been transformed to a more comprehensive and environmental integrated GDP measurement.